On Gender Justice and Gender Ideology: Proposals for a dialogue - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2017)
The present article, originally a lecture given at an event, consists of an approach on the theme “gender”, in which the author presents arguments in defense of the ideological character of various authors and positions of the so-called gender perspective. The approach contemplates an evaluation of several publications of the context of the Evangelical Church of Lutheran Confession in Brazil by the author. It shows that the struggle for human rights, especially for women’s rights in context of Christian churches, can and must be tackled without regard to the gender category in his ideological sense, and disregarding the approach given in the Beijing Declaration and Platform for Action (1995), and the Principles of Yogyakarta, but – as alternative – using only texts of the Charter of Human Rights. The argument points to the fragility of ecclesiastical discourse in favor of gender justice, since it presupposes one problematic concept of gender, which is not clearly distinguishable from the ideological meanings of the concept in contemporary society. The author ends by proposing to speak of social justice for men and women instead of gender justice. The article as a whole also reflects something of the state of the discussions and controversy on this subject in the Lutheran context.